Stereotypes about Intergenerational Cooperation in Companies: Case studies of Slovene companies - Mejaš, Ula; Ruzzier, Mitja; Škerlavaj, Miha (Naše gospodarstvo/Our economy, 2014)
Four generations are currently present in the labour market, and different events have affected their evolution. Theoretical backgrounds of stereotypes and generati- ons, as presented in this paper, serve as the basis for our qualitative research based on theoretical knowledge about generations, stereotypes, and intergenerational stereotypes. The research was carried out in different companies in Slovenia. In this paper, we present results of a study in which we examined three generations in the labour market. We explored whether the employees (subordinates and leaders) perceive the differences between the generations and what kinds they perceive. We compared the results with presented stereotypes and examined if stereotypes of generations exceed the actual differences between the generations raised by the interviewees in our study. Based on the findings, recommendations for practice and for further research are given.